The Periodization of Mongolia–Kazakhstan Political Relations (Mongolian Journal of International Affairs, 2025)
This study examines the evolution of political relations between Mongolia and Kazakhstan since the establishment of diplomatic ties in 1992. It analyzes how both countries, emerging from post-socialist transitions, gradually deepened their partnership- from initial consolidation to strategic alignment. By situating bilateral developments within broader regional and international dynamics, the study identifies the main factors shaping cooperation and evaluates their significance for small-state diplomacy in Central Asia. The analysis draws on political documents, high-level visits and their outcomes, official negotiations, and socio-political developments in both countries since the early 1990s. The development of Mongolia–Kazakhstan political relations can be understood through three historical phases: the first phase (1992-2008) was characterized by stable and steadily strengthening relations; the second phase (2009-2018) saw a slowdown yet continued stabilization; and the third phase (2019-present) marked a period of more active, dynamic, and intensified cooperation. Tracing these shifts reveals how bilateral interaction evolved in response to domestic transformations and changes in the regional environment. Overall, the study highlights how Mongolia and Kazakhstan have expanded cooperation, elevated their ties to a Strategic Partnership, and exercised diplomatic agency characteristic of small states seeking to enhance regional stability and diversify foreign relations.